2002
DOI: 10.1097/00042737-200210000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding peptic ulcers and presence of Helicobacter pylori by various tests: a case–control study

Abstract: NBPU patients had the highest prevalence of H. pylori by PCR. It seems unlikely that either H. pylori or the cagA-positive gene act as significant risk factors for bleeding in peptic ulcers. The lower prevalence of the microorganism among patients who bleed cannot be explained as an artificial finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…The greatest increase in risk was found by Santolaria et al [23], who reported a RR of 5.98 (95% CI: 2.9–12.3) in their study of 520 patients in secondary care in Spain. However, a fourth prospective study of 67 patients in Mexico found no association between H. pylori infection and hemorrhage [32]. …”
Section: Resultsmentioning
confidence: 99%
“…The greatest increase in risk was found by Santolaria et al [23], who reported a RR of 5.98 (95% CI: 2.9–12.3) in their study of 520 patients in secondary care in Spain. However, a fourth prospective study of 67 patients in Mexico found no association between H. pylori infection and hemorrhage [32]. …”
Section: Resultsmentioning
confidence: 99%
“…pylori cagA identification was carried out using the primers cagA1 (93089) (5Ј-ATACACCAACGCCTCCAAG-3Ј) and cagA2 (93261) (5Ј-TTGTTGCCG CTTTTGCTCTC-3Ј) as described by Castillo-Rojas et al (9).…”
Section: Methodsmentioning
confidence: 99%
“…In the time period (1998-2012), when eradication therapies were used in addition to PPIs, bleeding did not decrease; indeed its frequency was increased significantly (p<0.05). Despite new improved therapeutic modalities, this unexpected rise in bleeding may be due to other reasons; for example, H. pylori may not be the predominant etiologic factor in patients who experience complications requiring surgery (12,13). During the last decade, PU bleeding did not significantly change (2,5,14), but the incidence increased in patients older than 75 years of age (15).…”
Section: Original Articlementioning
confidence: 99%